A loss sensitivity factor method for locating ES in a distribution system with PV units - Sardi, Junainah; Mithulananthan, Nadarajah; Hung, Duong Quoc (IEEE Computer Society, 2016)
This paper presented an approach to place single and multiple Energy Storage (ES) units in a distribution network with photovoltaic (PV) units considering energy losses. The approach is based on ∆LSFmax, which is defined as a difference between the minimum and maximum Loss Sensitivity Factor (LSF) values. The GridLAB-D simulation software is used to model test systems under the study and to validate the proposed method. Results show that the proposed ∆LSFmax approach can yield lower energy losses and better voltage profiles than other methods: average LSF, centralized ES (i.e. ES is located at the substation) and ES located near the PV units. Some interesting results are also presented in the paper.